THE EFFECT OF RUPIAH EXCHANGE RATE ON INDONESIA EXPORT - Rahman Daffa, Raditya
This paper investigates the effect of Rupiah's exchange rate on Indonesia export, mainly export of base metal, export of palm oil and export of coal. The collapse of the Brenton woods agreement in 1973 has resulted in the floating exchange rate system. The currency has been allowed to move freely, such as appreciate and depreciate according to the market forces. Depreciation on the exchange rate will influence and affecting and resulted in increasing export performance where it will increase the export capacity and decrease its import and An appreciation, on the other hand, will decrease export performance hence decreasing export capacity and increase import (Sukirno, 2010). The main objective of this research is to analyse the effect and significance of exchange rate effects on Indonesia exports of base metal, palm oil and coal. This research include control variable such as GDP and Inflation. Multiple regression is conducted for this research to analyse the relationship between the Export as dependent variable and Exchange Rate, GDP and Inflation as Independent variable. Multiple regression analysis used Ordinary least square (OLS) as an analytical method to measure the correlation between variables and the hypotheses. The data spanning from 2010 Q1 to 2019 Q4 was used for this research. The result was revealed that exchange rate does not significantly affect the export of base metal, export of palm oil, and export of coal. In addition, GDP is found to significantly affect the export of base metal and palm oil export. However, GDP is not significant towards coal export. Furthermore, this research found GDP to have a positive relationship with the export of base metal, palm oil and coal. The result shows that inflation is having a significant effect on coal export, but inflation is insignificant towards the export of base metal and coal. In addition, this research found that inflation has a positive relationship towards export of base metal, palm oil and coal.